A case report of crystalline light chain inclusion-associated kidney disease affecting podocytes but without Fanconi syndrome: A clonal analysis of pathological monoclonal light chain. Issue 5 (February 2019) - Ito, Kiyoaki; Hara, Satoshi; Yamada, Kazunori; Zoshima, Takeshi; Mizushima, Ichiro; Fujii, Hiroshi; Miyazaki, Ryoichi; Kawai, Yasukazu; Yachie, Akihiro; Nagata, Michio; Izui, Shozo; Yamagishi, Masakazu; et al.
Abstract: Rationale: Crystalline light chain inclusion-associated kidney disease affects mainly tubular epithelial cells and is often clinically manifested as Fanconi syndrome. However, only very few case reports about the crystalline deposits within the podocytes are available, and the nature of the pathogenic monoclonal light chain implicated in these cases is still unknown. We report a case of crystalline inclusion-associated kidney disease manifested as crystalline podocytopathy in which we identified the complete structure of the pathogenic monoclonal light chain as belonging to the germ-line gene of Vκ1-39. Patient concerns: We describe a 65-year-old woman with crystalline light chain inclusion-associated kidney disease showing mild proteinuria and renal insufficiency with monoclonal gammopathy of undetermined significance without Fanconi syndrome. She had crystalline inclusions mainly within podocytes, tubular epithelial cells and histiocytes in the kidney. Light microscopy showed vacuolation of podocytes and tubular epithelial cells, while eosin negative pale needle-like crystals were present within these cells. Electron microscopy showed accumulation of club-like crystals with high electron density in podocytes, proximal tubular epithelial cells and interstitial histiocytes. Clonal analysis revealed that a pathogenic monoclonal light chain was derived from germline gene, Vκ1-39. Diagnoses: The diagnosis of crystalline light chain inclusion-associated kidney disease was made. Interventions and outcomes: Bortezomib and dexamethasone were started and her renal function improved to eGFR 36 mL/min/1.73 m 2 after 9 courses of therapy. Lessons: Patients with light chain crystalline podocytopathy may have a similar pathogenic monoclonal light chain derived from the same germline gene, Vκ1–39, to that of patients with light chain proximal tubulopathy.